Arbitrators' impartiality and independence: commentary on Gobowen v AXXIS. (16th March 2018) - Akeredolu, Abimbola; Umeche, Chinedum Ikenna
Abstract: The recent decision of the Federal High Court, a court of first instance, in Gobowen has brought to the fore the issue of arbitrators' impartiality and independence. The court annulled an award because one of the arbitrators failed to disclose his family relationship with the lead counsel for the party who appointed him. This is possibly the first case in Nigeria where the issue for determination turned on the question of arbitrators' impartiality and independence. The article interrogates the rationale for the court's conclusion. Although the authors agree with the court, they query certain aspects of the court's analyses. Judgments of courts of first instance are hardly reported in Nigeria. Yet, they establish precedents on the points decided. The commentary is intended to give the decision a wider audience, especially in the light of the increased use of arbitration as a means of resolving disputes in Nigeria